2019
DOI: 10.1051/0004-6361/201834003
|View full text |Cite
|
Sign up to set email alerts
|

A ring in a shell: the large-scale 6D structure of the Vela OB2 complex

Abstract: Context. The Vela OB2 association is a group of ∼10 Myr stars exhibiting a complex spatial and kinematic substructure. The all-sky Gaia DR2 catalogue contains proper motions, parallaxes (a proxy for distance), and photometry that allow us to separate the various components of Vela OB2. Aims. We characterise the distribution of the Vela OB2 stars on a large spatial scale, and study its internal kinematics and dynamic history. Methods. We make use of Gaia DR2 astrometry and published Gaia-ESO Survey data. We app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 78 publications
5
39
1
Order By: Relevance
“…The eastern subgroup is denser and elongated. The western, sparser subgroup appears to occupy the cavity inside the ring-like structure reported by Cantat-Gaudin et al (2019). Its projection also coincides with the structure known as the IRAS Vela Shell, and it could be the host population of the supernova that initiated the expansion of the shell.…”
Section: Population IIIsupporting
confidence: 60%
See 2 more Smart Citations
“…The eastern subgroup is denser and elongated. The western, sparser subgroup appears to occupy the cavity inside the ring-like structure reported by Cantat-Gaudin et al (2019). Its projection also coincides with the structure known as the IRAS Vela Shell, and it could be the host population of the supernova that initiated the expansion of the shell.…”
Section: Population IIIsupporting
confidence: 60%
“…Armstrong et al (2018) studied the distribution of the stars coeval with the Gamma Velorum cluster, and compared it with the Vela OB2 stars of de , noting that the OB stars are not all located in high-density regions of young PMS stars. Finally, Cantat-Gaudin et al (2019) identified 11 distinct groups in 3D positional and velocity space, spread over more than a hundred parsecs, and confirmed that their overall structure is expanding. The centre of this structure appears devoid of stars, and its projection on the sky matches the large bubble known as the IRAS Vela Shell (IVS, Sahu 1992).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Such sub-groups could be separated into seven main groups of ages between 10 and 50 Myr. Guided by our discovery of a new cluster, BBJ 1, here we expand the study of Cantat-Gaudin et al (2019a) and Cantat-Gaudin et al (2019b) to a wider area, reaching l ∼ 220. We find that BBJ 1 is coeval to NGC 2547 but it is located at a distance of ∼260 pc from it.…”
Section: Relic Stellar Filamentmentioning
confidence: 99%
“…A blue line connects the major filamentary structure that is confined in range of distance ∼320 to ∼420 pc from us while the distance between the clusters are the two extremes of the structures (BBJ 1 and NGC 2547) is ∼260 pc. Cantat-Gaudin et al (2019a) and Cantat-Gaudin et al (2019b) used the information available with the Gaia DR2 data to study the kinematic structure of the seven populations that were the focus of their study. They find signs of expansion along the Galactic X and Z axes for the whole structure.…”
Section: Relic Stellar Filamentmentioning
confidence: 99%